Management of recurrent urolithiasis: advances in prevention strategies - Alghamdi, Abdulrhman Mastoor; Alqurashi, Enad Ajlan; Alsubaie, Abdulhadi Turki; Alamri, Abdulrahman Mohammed; Alamri, Abdulrahim Mohammed; Abdulmajeed, Abdulaziz Hussain; Asiri, Saeed Abdullah; Alenezi, Nayef Khaled (International Journal Of Community Medicine And Public Health, 2025)
Recurrent urolithiasis is a chronic and extremely common condition that is characterized by the development of calculi in the urinary tract. It poses a serious health burden, affecting roughly 10-15% of the world’s population and having recurrence rates of over 50% within five years. Therefore, minimizing recurrence, enhancing patient outcomes, and lowering healthcare costs all depend on effective prevention strategies. Conventional preventative strategies emphasize lifestyle modifications like drinking more water, consuming less protein and sodium, and consuming oxalate-rich foods in moderation. Pharmacological strategies such as citrate supplementation, thiazide diuretics, and allopurinol have demonstrated promise; however, new data raises doubts about the effectiveness and adverse effect profiles of some regimens. Additionally, new studies emphasize the significance of tailored interventions based on genetic susceptibility, metabolic assessment, and urine biochemistry. Prospective avenues for the future include probiotics that decrease oxalate absorption, genomic profiling techniques, and engagement of machine learning and algorithms to identify high-risk individuals. This review thoroughly explores both conventional and cutting-edge approaches to the changing field of recurrent urolithiasis prevention. It highlights how important multidisciplinary care, customized treatment planning, and routine follow-up are to the success of stone prevention.